Molecular-genetic characterization of Ukrainian patients with mucopolysaccharidosis I: identification of three new mutations in α-L-iduronidase gene - Trofimova, N.S.; Olkhovich, N.V. (Вiopolymers and Cell, 2016)
Mucopolysaccharidosis I (MPS I) is a rare hereditary autosomal-recessive metabolic disorder, which occurs due to the deficiency of the lysosomal enzyme α-L-iduronidase (IDUA; EC 3.2.1.76). There are three clinical forms of MPS I: Hurler syndrome, MPS I H; MIM # 607014, ORPHA 93473, Hurler/Scheie syndrome, MPS I H/S; MIM # 607015, ORPHA 93476, Scheie syndrome, MPS I S; MIM # 607016, ORPHA 93474. Aim. To identify the spectrum of mutations in the IDUA gene in Ukrainian patients with MPS I. Methods. RFLP-analysis, automated sequencing. Results. We have identified 100 % (34/34) mutant alleles of the IDUA gene among 18 Ukrainian patients (one proband had a sibling with the identical genotype) with MPS I from 17 families. The spectrum of mutations in the IDUA gene in Ukrainian patients with MPS I is represented by six known missence mutations: p.Q70*, p.W402*, p.A75T, p.A327P, p.P533L, p.S633I; two deletions: c.1398delC and c.46_57del_12, one insertion: c.889_899_ins_12, and one mutation in the splicing zone IVS11ds+5G–A. Three new missence mutations were revealed by us in the IDUA gene: p.N372S, p.Q563P and p.S633*. Conclusions. Our results may be used for planning the most reasonable algorithm of the molecular-genetic analysis of Ukrainian patients with MPS I.